(untitled) (JIMP : Jurnal Ilmiah Manajemen Pancasila, 2024)
This research aims to marketing on purchasingl decisions for Corkcicle products in Indonesia. Thisl research isl quantitative lresearch. Thel population usedl in thisl research werel consumers whol played social media TikTok and had purchased Corkcicle products, with al sample size ofl 112 respondentsl using thel Rao Purba lformula. Thel data collection methodl is through questionnaires. This research uses thel SmartPLS l3.0l analysis technique. Thel results ofl this research show thatl product qualityl has al positive andl significant effectl on purchasingl decisions withl a lT-Statistic valuel of l2.494 (> 1.96) andl P- Values l0.013 (< 0.05), pricel has al positive andl significant effectl on purchasingl decisions withl a lT-Statistic valuel of 1.989 (>1.96) andl P-Values l0.047 (<0.05), Social media marketingl is positivel and significantl on purchasingl decisions withl a lT-Statisticl value ofl 3.042 (>1.96) and lP-Values l0.002 (<0.05), Thel variables product quality, pricel and sociall media marketingl simultaneously havel a significantl influence onl purchasing decisionsl with calculated F of 108 > F table of 2,69.